Antimalarial Activity of Kaempferol and Its Combination with Chloroquine in Plasmodium berghei Infection in Mice. (2nd December 2018) - Somsak, Voravuth; Damkaew, Awatsada; Onrak, Pinanong
Abstract : The search for new antimalarial drugs has become an urgent requirement due to resistance to the available drugs and the lack of an effective vaccine. In this respect, the present study aimed to evaluate the antimalarial activity of kaempferol against Plasmodium berghei infection in mice as an in vivo model. Chronic toxicity and antimalarial activities of kaempferol alone and in combination with chloroquine were investigated in P. berghei ANKA infected ICR mice using standard procedures. The results showed that chronic administration of 2, 000 mg/kg of kaempferol resulted in no overt signs of toxicity as well as no hepatotoxicity, nephrotoxicity, or hematotoxicity. Interestingly, kaempferol exerted significant ( P < 0.05) chemosuppressive, chemoprophylactic, and curative activities in a dose-dependent manner. The highest antimalarial activity was found at a dose of 20 mg/kg which resulted in a significantly ( P < 0.05) prolonged survival of infected mice. Moreover, combination treatment of chloroquine and kaempferol also presented significant ( P < 0.05) antimalarial effects, although the effects were not significantly different from the chloroquine treated group. From the results of the present study, it can be concluded that kaempferol possesses acceptable antimalarial activities. However, further investigation should be undertaken on the mechanism responsible for the observed antimalarial activity.